Short communication.Variability of fatty acid and mineral content in linseed (Linum usitatissimum) lines from a range of European sources - Kiralan, M.; Gokpinar, F.; Ipek, A.; Bayrak, A.; Arslan, N.; Kok, M. S. (Spanish Journal of Agricultural Research, 2010)
Linseed (Linnum usitatissimum) has recently gained popularity as a health food product. It has high levels of fatty acids and minerals, giving it characteristics beneficial for functional foods. This research is a comparative analysis of the fatty acid and mineral content of 23 European linseed lines. The levels of seven fatty acids were analysed using an Agilent 6890 N GC. Alfa-linolenic acid (ALA) (C18:3, n-3) was the most predominant, ranging from 49.4 to 56.4%, followed by oleic (C18:1, n-9; 19.8 to 28.8%), linoleic (C18:2, n-6; 10.8 to 16.0%), palmitic (C16:0, 4.1 to 6.2%) and stearic (C18:0, 3.3 to 7.1%) acids. In contrast arachidonic (C20:0) and gadoleic (C20:1) acids were only found at trace levels. One-way ANOVA test showed significant differences between the lines in terms of saturated and unsaturated fatty acid content (p < 0.05). A negative correlation (r = –0.74) exists between levels of ALA and oleic acid. The levels of ten minerals (Ca, Mg, Na, K, P, Cu, Fe, Mn, Zn and B) were also determined and showed significant variability between lines. The results can be used to assist variety selection in targeted breeding programs.